Prevention - Cynn, Christine (The Ohio State University Press, 2018)
Approximately 70% of the global total of people living with HIV/AIDS in 2016 were in sub-Saharan Africa. After delayed governmental responses, the media has been consistently deployed as an essential tool for prevention. But HIV prevention campaigns reflect multiple conflicting and shifting agendas that encompass far more than the imparting of information about how to limit the spread of the virus. In Prevention: Gender, Sexuality, HIV, and the Media in Côte d'Ivoire, Christine Cynn draws from postcolonial, queer, and feminist film and media studies to critique global HIV prevention efforts and how they attempt to reshape gendered sexualities and notions of family in line with the rationality of neoliberalism.